Measuring off-Balance-Sheet Leverage - Breuer, Peter (Washington, D.C. : International Monetary Fund, 2000)
The simultaneous unwinding of leveraged positions can trigger financial market turbulence. Although balance-sheet measures of leverage are available, it is useful to construct a measure of leverage that incorporates both on- and off-balance-sheet activities. This paper provides measures of leverage implicit in derivative contracts by decomposing the contracts into cash market equivalent components. A leverage ratio can then be calculated for this replicating portfolio, which consists of own funds (equity) and borrowed funds equivalents (debt). Methods for aggregating leverage by institution and by markets are presented. The interaction between leverage and risk is discussed, and a modified capital adequacy ratio is calculated, which captures off-balance-sheet exposure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet